A forgotten collection: the Libyan ethnobotanical exhibits (1912-14) by A. Trotter at the Museum O. Comes at the University Federico II in Naples, Italy - De Natale Antonino; Pollio Antonino (BMC, 2012)
Abstract Background The Ethnobotanical Collection from the Libyan territories of the botanist Alessandro Trotter is included in the Oratio Comes Botanical Museum at the Faculty of Agraria at the University Federico II in Naples. Trotter explored different territories of Libya, mainly Tripolitania, between 1912-1924, collecting plant specimens and the drugs most frequently sold in the markets. The Libyan herbarium currently includes over 2300 sheets of mounted and accessioned plants. The drugs, mostly acquired by Trotter from Tripolitanian markets, were identified and packed in 87 paper sheets or boxes. Trotter added ethnobotanical information for each species when available. Methods A database of the herbarium species and the drugs has been carried out, after a taxonomic update. Nomenclature has been revised according to the African flowering plants database and the World Checklist of selected plant families, and a comparison with currently available ethnopharmacological data from North African has been attempted. Results In this study, ethnopharmacological data related to about 80 species of flowering plants and to 4 lichens are presented. The plants are mainly from Mediterranean or Sub-Saharan habitats and belong to 37 different families; Lamiaceae was the most cited family, with 10 accessions. Generally, the aerial parts of the plants are the most frequently used (28 species), followed by leaves (15 species), flowers and seeds (9 species), fruits (7 species) and hypogean organs (roots, rhizomes, tubers: 5 species). Plants were generally processed in very simple ways: infusion or decoction of the plants were prepared and orally administered or used for topical applications. A wide range of conditions was treated, ranging from mental disorders to skin affections. All the organs of human body are considered, but the pathologies of gastro-intestinal tract, respiratory system and those related to traumatic accidents were the most frequently mentioned. The comparison with the recent ethnopharmacological research in Maghreb and its neighboring countries reveals a high correspondence; almost all the plants cited by Trotter are still used in the folk medicine of at least one of the North African countries, and the therapeutic uses of each plant appear consistent over time. Conclusions The information collected by Trotter is an important contribution to tracing plant utilization in Libyan folk medicine over the last century.